1995
DOI: 10.1002/mc.2940140403
|View full text |Cite
|
Sign up to set email alerts
|

Mutational specificity of 1‐(2‐chloroethyl)‐3‐cyclohexyl‐1‐nitrosourea in the Escherichia coli lacl gene of O6‐alkylguanine‐DNA alkyltransferase‐proficient and ‐deficient strains

Abstract: Forward mutations induced by 1-(2-chloroethyl)-3-cyclohexyl-1-nitrosourea (CCNU) in the lacl gene of Escherichia coli were recovered from bacteria proficient (Ogt+ Ada+) and deficient (Ogt- Ada-) in O6-alkylguanine-DNA alkyltransferase activity. A CCNU dose of 1 mM was selected for DNA sequence analysis. A total of 245 induced mutations were characterized. The mutations were almost exclusively (95%) GC-->AT transitions, indicating that CCNU-induced mutations arose in bacteria primarily from misreplication of O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

1997
1997
2001
2001

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…At both loci, the incidence and the location of GC4AT transitions are consistent with the hypothesis that O6-alkylguanine is the main determinant of CCNU mutagenicity. Alkylnitrosoureas preferentially cause GC4AT transitions at Gs preceded by a Pu residue in E. coli (Jurado et al, 1995;RoldaÁ n-Arjona et al, 1994;Richardson et al, 1987;Burns et al, 1988) and in eukaryotes (Inga et al, 1995;Kunz and Mis, 1989;Minnick et al, 1992;Moriwaki et al, 1991;Palombo et al, 1992). The 5'-¯anking purine eect has been explained as the consequence of a structural in¯uence on the initial formation of O6-alkylguanine, which may be further enhanced by alkylation speci®c repair (Horsfall et al, 1990).…”
Section: Discussionmentioning
confidence: 99%
“…At both loci, the incidence and the location of GC4AT transitions are consistent with the hypothesis that O6-alkylguanine is the main determinant of CCNU mutagenicity. Alkylnitrosoureas preferentially cause GC4AT transitions at Gs preceded by a Pu residue in E. coli (Jurado et al, 1995;RoldaÁ n-Arjona et al, 1994;Richardson et al, 1987;Burns et al, 1988) and in eukaryotes (Inga et al, 1995;Kunz and Mis, 1989;Minnick et al, 1992;Moriwaki et al, 1991;Palombo et al, 1992). The 5'-¯anking purine eect has been explained as the consequence of a structural in¯uence on the initial formation of O6-alkylguanine, which may be further enhanced by alkylation speci®c repair (Horsfall et al, 1990).…”
Section: Discussionmentioning
confidence: 99%
“…Differences in survival and mutability between uvr + and uvrbacteria [27][28][29] as well as between ATase + and ATasebacteria have been reported [9,29]. On the other hand, Kohda et al [30] found that uvrAand uvrA + strains treated with chloroethyl-nitrosourea showed no differences in survival and mutability.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, all strains we examined had similar incidences of GC→AT transitions ( Table 2) that occurred in similar sequence contexts (more than 96% were preceded 5´ by a purine) ( Table 4). It is known that alkylnitrosoureas preferentially cause GC→AT transitions at Gs preceded by a purine residue in E. coli [9,32,33] and in eukaryotes [1,34,35]. The 5´-flanking purine effect has been explained as the consequence of structural influence on the initial formation of O 6 -chloroethylguanine that may be further enhanced by sequence-specific repair [36].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations